Kynurenic Acid Accelerates Healing of Corneal Epithelium In Vitro and In Vivo - Anna Matysik-Woźniak; Waldemar A. Turski; Monika Turska; Roman Paduch; Mirosław Łańcut; Paweł Piwowarczyk; Mirosław Czuczwar; Robert Rejdak (MDPI AG, 2021)
Kynurenic acid (KYNA) is an endogenous compound with a multidirectional effect. It possesses antiapoptotic, anti-inflammatory, and antioxidative properties that may be beneficial in the treatment of corneal injuries. Moreover, KYNA has been used successfully to improve the healing outcome of skin wounds. The aim of the present study is to evaluate the effects of KYNA on corneal and conjunctival cells in vitro and the re-epithelization of corneal erosion in rabbits in vivo. Normal human corneal epithelial cell (10.014 pRSV-T) and conjunctival epithelial cell (HC0597) lines were used. Cellular metabolism, cell viability, transwell migration, and the secretion of IL-1β, IL-6, and IL-10 were determined. In rabbits, after corneal de-epithelization, eye drops containing 0.002% and 1% KYNA were applied five times a day until full recovery. KYNA decreased metabolism but did not affect the proliferation of the corneal epithelium. It decreased both the metabolism and proliferation of conjunctival epithelium. KYNA enhanced the migration of corneal but not conjunctival epithelial cells. KYNA reduced the secretion of IL-1β and IL-6 from the corneal epithelium, leaving IL-10 secretion unaffected. The release of all studied cytokines from the conjunctival epithelium exposed to KYNA was unchanged. KYNA at higher concentration accelerated the healing of the corneal epithelium. These favorable properties of KYNA suggest that KYNA containing topical pharmaceutical products can be used in the treatment of ocular surface diseases.